Zimbabwe National Water ICT Workshop Management System. - Rashirai, Perpetua (Midlands State University, 2017)
Zimbabwe National Water Authority ICT workshop was facing challenges with computers pilling up in the workshop due to technicians not being held liable for repairs. Several alternatives were considered to develop the system which included outsourcing, in-house development, improving the current system and in-house development proved to be best amongst the alternatives. A feasibility study was carried out using the economic, operational, technical and social feasibility techniques and from the results it was deemed viable to carry out the system development. Several information gathering techniques such as interviews, questionnaires, observation and document inspection were used to get an understanding of how the current system works and it assisted in formulating functional and non functional requirements. Php and MySQL were used to develop the workshop management system. Implementation was done using the parallel conversion to reduce the risk of loss of information. Continuous maintenance of the workshop management system will be done using the adaptive method because of its flexibility to adopt software package to different operating environment. It is the aspiration of the researcher to add an auctioning module for unwanted machinery.